EVALUATION OF MINERALS AS MANURE VALUE OF FAECAL MATTER OF CHICKS FED WITH MOLLUSCAN SUPPLEMENTARY DIET - AKARTE. S.R.; R.B. BAHADURE (International Journal of Pharma and Bio Sciences, 2015)
The mineral matters of body comprise a large number of elements present in varying amounts in different parts, according to the function they perform and some are passed out along with faecal matter which is having prime importance as animal manure–value for application in agricultural field. Poultry manure is an excellent source of nutrients and can be incorporated into most fertilizer programs. With the view point of this chicken faecal matter was assessed after providing them additional molluscan diet i.e. dried flesh of whole body mass and the grinded shell crush of bivalve, Lamellidens marginallis, as nonconventional food added in normal grains such as Wheat , maize , Jawar , Bajara and beans, searals etc. For comparative assessment of mineral contents in faecal matter of chicks, thirty days feeding to five different groups of chicks was performed with different diet contents such as conventional food-grains, poultry farm recommended commercial food, supplementary fish food and supplementary 10% and 20% molluscan diet. After 30 days feeding, faecal matter of these chicks was assessed for minerals in it. It was observed that phosphorus contained in faecal matter was higher only in grain- fed chicks, whereas sodium and potassium was lower in grain- fed and 10% molluscan diet fed chicks as compared to other groups. Calcium was higher in 10% and 20% molluscan diet fed chicks than other groups.